2006
DOI: 10.1111/j.1439-0418.2006.01057.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential for mating disruption to reduce cone damage by the spruce seed moth, Cydia strobilella, in spruce seed orchards

Abstract: The spruce seed moth, Cydia strobilella (L.), is a serious and widely distributed pest of spruce seed orchards in North America and Europe. Current pest management activities in seed orchards rely mainly on chemical pesticides for insect control. Mating disruption with sex pheromone is a potential alternative pest management tool for C. strobilella. In 2002, field tests confirmed that sticky traps baited with 3 lg of (E)-8-dodencenyl acetate (E8-12:Ac), the sex pheromone of C. strobilella, could capture males … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Because of the extremely high sensitivity of males to the pheromone, and the low female pheromone production, efficient mating disruption may be easier to obtain for C. strobilella compared to many other moth species. Trudel et al (2006) used this technique in white spruce seed orchards in Canada to reduce cone damage by C. strobilella. Male captures in pheromone traps were reduced by up to 98%, and cone damage was reduced by up to 69% in pheromone-treated areas compared to control areas, thus showing the potential of the mating disruption technique to control populations of C. strobilella in European seed orchards as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the extremely high sensitivity of males to the pheromone, and the low female pheromone production, efficient mating disruption may be easier to obtain for C. strobilella compared to many other moth species. Trudel et al (2006) used this technique in white spruce seed orchards in Canada to reduce cone damage by C. strobilella. Male captures in pheromone traps were reduced by up to 98%, and cone damage was reduced by up to 69% in pheromone-treated areas compared to control areas, thus showing the potential of the mating disruption technique to control populations of C. strobilella in European seed orchards as well.…”
Section: Discussionmentioning
confidence: 99%
“…(Z)-8-Dodecenol (Z8-12: OH) was reported as an attractant in the Netherlands (Booij and Voerman 1984), and in Poland (Skrzypczynska et al 1998). In Canada, (E)-8-dodecenyl acetate (E8-12:OAc) was demonstrated to be an attractant (Grant et al 1989), and later this compound was confirmed as a sex pheromone for C. strobilella (Bédard et al 2002;Trudel et al 2006). In China, where the species heavily infests cones of Korean spruce, P. koraiensis Nakai, field trapping tests revealed an attractant blend of Z8-12:OH, (E)-8-dodecenol (E8-12:OH), and (8Z,10E)-dodecadienol (Z8,E10-12:OH) (Sun et al 2001).…”
Section: Introductionmentioning
confidence: 93%
“…In our initial experiments on C. strobilella , we used a similar experimental protocol (type of disruption dispenser, dispenser density, dose of pheromone, size of treated area) compared to those used in the mating disruption experiments on C. youngana performed in Canadian spruce seed orchards (Trudel et al 2006 ). In that study, the reduction in trap catch in the pheromone-treated area versus control area (87–98%) was generally less pronounced compared to our study, and catches in a treated area could be as high as 27 males per trap (Trudel et al 2006 ). In spite of this lower level of communication disruption based on trap catches, a significant reduction in cone damage in the treated plot versus control plot was achieved for both years of the study (55 and 69%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Cydia strobilella : These initial field tests were conducted in Maltesholm and Ålbrunna to investigate if treatment with disruption dispensers resulted in a reduction in trap catch compared to non-treated control areas and if such effect disappeared when dispensers were removed. At each location, 1 ha (100 m × 100 m) was treated with pheromone and the treated area and the control area were separated by at least 200 m. In the treated area, rubber septa loaded with 1 mg each of E 8, E 10-12:OAc and E 8, Z 10-12:OAc (compensated for differences in isomeric purity of compounds) were placed in an 8 × 8 matrix, giving a density of 64 point sources per ha (similar to the density used by Trudel et al 2006 ). Two different mating disruption regimes were tested, suspending the dispensers at 2 m or 4 m height.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation